Neurofilament light as a biomarker for motor decline in Parkinson’s disease - Liu, Yumei; Dou, Kaixin; Xue, Ling; Li, Xiaoyuan; Xie, Anmu (Frontiers in Neuroscience, 2022)
Objectives: To determine whether NfL could reflect motor decline and compare the predictive values of CSF and serum NfL in PD individuals. Methods: CSF/serum samples were collected from PD patients and healthy controls (HCs) with motor assessments at baseline and after three years of follow-up from the PPMI. Multiple linear regression models and linear mixed-effects models were used to investigate the associations of motor assessments with baseline and longitudinal CSF/serum NfL. Associations between the change rates of motor assessments and CSF/serum NfL were further investigated via multiple linear regression models. Mediating effect analysis was used to research whether CSF α-syn acts as the mediator between NfL and motor assessments. Results: We found PD patients had higher baseline CSF/serum NfL levels than HCs. Both baseline CSF/serum NfLs and their change rates predicted measurable motor decline in PD assessed by different motor scores. Baseline serum NfL and its rate of change were strongly associated with CSF NfL levels in PD patients (P < 0.001). Besides, there were also significant differences in CSF/serum NfL levels and predicted values of motor decline between PD males and females. Mediating effect analysis showed CSF α-syn mediated the effect of CSF NfL on total UPDRS scores and UPDRSIII with 30.6% and 20.2% mediation, respectively. Conclusion: Our results indicated that NfL, especially serum NfL concentration, could serve as an easily accessible biomarker to monitor the severity and progression of motor decline in PD individuals, especially in PD males. Besides, CSF α-syn acts as a mediator between NfL and motor progression.